EFEKTIFITAS PENGGUNAAN APLIKASI MICROSOFT EXCEL DALAM PENGELOLAAN NILAI RAPOR DI SMA PGRI CICURUG - Morisson, Buci; Sutirman (CV SWA Anugerah, 2024)
One of the most renowned and frequently used tools for data processing is Microsoft Excel. The purpose of this study is to evaluate how well instructors at SMA PGRI Cicurug perceive Microsoft Excel as a tool for processing student report card data. The survey employed a Likert Scale, with the research analysis adopting a quantitative descriptive approach. The methodology involved calculating data percentages using frequency distribution and intervals before providing a comprehensive explanation. The findings of the study indicate that participants view Microsoft Excel as an efficient tool for processing student report cards at SMA PGRI Cicurug. Training is essential to enhance teachers' proficiency with Microsoft Excel, as utilizing this program for processing student report cards can simplify their tasks in managing and processing report card data. Keywords: Microsoft Excel, Report Value , Data Processing Media